Morphological Alterations in the External Gills of Some Tadpoles in Response to pH - Thabah, Caressa Maebha; Devi, Longjam Merinda; Hooroo, Rupa Nylla Kynta; Dey, Sudip (Journal of Morphological Sciences, 2018)
Introduction Water pH affects the breeding, hatching, development, locomotion, mortality and habitat distributions of species in nature. The external gills of anuran tadpoles were studied by several authors in relation to abiotic factors. Exposure to low and high pH has been found to adversely affect the different tissues of various organisms. On that consideration, the present investigation was performed with tadpoles of the species Hyla annectans and Euphlyctis cyanophlyctis.Material and Methods The maximum and the minimum pH thresholds were determined prior to the detailed experiments on the effects of pH. The pH that demonstrated 50% mortality was taken as the minimum and maximum pH thresholds. The hatchlings of both the species were then subjected to different pH (based on the minimum and maximum pH thresholds). After 48 hours of exposure, the external gills of the hatchlings were anesthetized and observed under a scanning electron microscope.Results After 48 hours, clumping, overlapping and curling of the secondary filaments of the external gills and epithelial lesions in response to both acidic and alkaline pH were observed. The lengths of the secondary filaments were also affected by pH in both the species studied when compared with the control groups.Conclusion Scanning electron microscopic approaches are relevant in assessing the adverse effects of pH on the morphology of the external gills of H. annectans and E. cyanophlyctis tadpoles, which included problems with osmoregulation, acid-base balance and respiratory function.
Keywords: Hyla annectans; Euphlyctis cyanophlyctis; low pH; high pH; scanning electron microscopy